Ranging behaviour of Rattus novergicus using radio-telemetry in wet market at Petaling Jaya - Mohd Salim, Nurul Awatif (2016)
Rodents are found everywhere and they make up two fifths of all known mammal species (Tweedie, 1978). Their characteristic feature is the dental form and arrangements. Their teeth and their handy fore feet give them great efficiency in causing damage. Rattus norvegicus has spread over the past decades and established themselves along routes of human migration and now can be found everywhere (Yoshida, 1980). They can be the main sources of several zoonotic pathogens which constitute a menace to public health, and recently, rising cases of leptospirosis. The objective of this study is to understand the behavior of R. norvegicus. The first aspect of behavioral study is the foraging behavior and pattern of habitat use. Radio telemetry is used to map the home range and to investigate the activity pattern of R. norvegicus. Three rats (one male and two females) in and around the wet market at Jalan Othman were captured using cage trap and anaesthetized for identification purpose. Radio transmitters of specific frequencies were attached to the rats. Radio tagged rats were then followed from 1930 hrs to 2230 hrs or 6-7 hours over seven days to mark the locations and extension of the area covered. The home range size and the core area were estimated using MCP (Minimum Convex polygon) and HM (Harmonic Mean) method. While the home ranges analysis of the captured rats were calculated using the Biotas of the Ecological Software Solutions Inc software. This study showed that male rat has bigger home range size than female rat. This condition is being influenced due to reasons of food abundance in several spots and high population density. And throughout this study also display that both male and female R.novergicus are more active on the early night after sunsets.